Minimum Roman Dominating Distance Energy of A Graph - R, Lakshmanan; N, Annamalai (IndoMS, 2023)
In this correspondence, we introduced the concept of minimum roman dominating distance energy ERDd(G) of a graph G and computed minimum roman dominating distance energy of some standard graphs. Also, we discussed the properties of eigenvalues of a minimum roman dominating distance matrix ARDd(G). Finally, we derived the upper and lower bounds for ERDd(G).